Atlas Florae Europaeae notes 30. Resurrection and typification of the name Sorbus semipinnata Borbás (Rosaceae) - Somlyay, Lajos; Sennikov, Alexander N. (Phytotaxa, 2016)
The name Sorbus dacica Borbás (1887: 404), which refers to a well-defined species endemic to Romania, is widely accepted (e.g. Jávorka 1924–1925, Nyárády 1939, Kárpáti 1940, 1960, Buia 1956, Warburg & Kárpáti 1968, Dihoru & Pârvu 1987, Ciocârlan 2009, Dihoru & Negrean 2009, Kurtto 2009, Sârbu et al. 2013). This species is supposed to be of hybrid origin between some taxa of S. subgen. Aria Persoon (1806: 38) and S. aucuparia Linnaeus (1753: 477) of S. subgen. Sorbus; such hybrids and stabilized hybridogenous species are currently classified in S. subgen. Soraria Májovský & Bernátová (2001: 21).